Routes of Kuçedra: Relation to Water and Authority in Contemporary Albania - Gregorič Bon, Nataša (Traditiones, 2020)
The article takes the reader along the multitude of entanglements between the social, political, economic, infrastructural, scientific, and mythological meanings of water in Albania. Waterways, along with the routes of the mythical water figure called Kuçedra, continuously bring to the shore the meaning and the relation to authority. The latter used to be an essential part of the unwritten laws or the so-called Kanuns that were managed by the big men of particular patrilines. The article argues that the relation to authority is deeply rooted in the structural terrains of the Albanian society. The changing nature of the water (in similar ways to Kuçedra) always manages to trickle down, permeate, entangle and transgress these ambiguities and generate space-time in contemporary Albania.